Distress and Therapeutic Outcomes Among Transgender and Gender Nonconforming People of Color. (January 2019) - Lefevor, G. Tyler; Janis, Rebecca A.; Franklin, Alexis; Stone, William-Michael
Transgender and gender nonconforming (TGNC) People of Color experience stressors unique to both TGNC and racial and/or ethnic minority communities, resulting in disparities in mental health. Guided by minority stress and intersectionality theories, we examined initial anxiety and depression, as well as changes in symptoms, in 41, 691 clients from the Center for Collegiate Mental Health 2012–2016 dataset. We sought to understand disparities that may exist in distress and therapeutic response between TGNC and cisgender clients. We also examined the intersection of gender and racial and/or ethnic identities to examine how these trends differ for TGNC People of Color. Results from hierarchical linear modeling indicated greater symptom severity, but a slower remission of symptoms of depression and anxiety, among TGNC clients. Interaction effects were nonsignificant; however, TGNC Clients of Color experienced more distress than either White TGNC clients or cisgender Clients of Color. On average, TGNC clients, compared to cisgender clients, utilized an additional 2.5 sessions of therapy.